Care manager role for older multimorbid heart failure patients’ needs in relation to psychological distress and quality of life: a cross-sectional study - Gostoli, Sara; Subach, Regina; Guolo, Francesco; Bernardini, Francesco; Cammarata, Alessandra; Gigante, Graziano; Herbeck Belnap, Birgit; Della Riva, Diego; Urbinati, Stefano; Rafanelli, Chiara (Frontiers in Cardiovascular Medicine, 2024)
Background: There are few studies investigating patients’ needs in healthcare focusing on disease severity and psychological characteristics of elderly heart failure (HF) patients with multimorbidity, specifically addressed by a care manager (CM). Aim(s): To explore the role of a CM dealing with elderly multimorbid HF patients’ needs/preferences according to NYHA class, ejection fraction, psychological/psychosomatic distress and quality of life (QoL), utilizing a Blended Collaborative Care (BCC) approach (ESCAPE; Grant agreement No 945377). Methods: Cue cards, self-reported questionnaires, and a semi-structured interview were used to collect data. Results: Twenty-five Italian patients (mean age±SD = 77.5±6.68) were enrolled between June 2021 and March 2022. The most relevant patients’ needs to be addressed by a CM were: education (e.g., on medical comorbidities), individual treatment tailoring (e.g., higher number of appointments with cardiologists) and symptom monitoring. Conclusion: The study highlights the importance of targeting HF patients' needs according to psychological characteristics, whose healthcare requires person-centered care with CM assistance. In view of ESCAPE BCC intervention, a CM should consider specific patients’ needs of elderly multimorbid HF patients with psychological, psychosomatic distress, particularly somatization, and lower QoL to achieve a more personalized health care pathway. Study registration: The «Evaluation of a patient-centred biopsychosocial blended collaborative care pathway for the treatment of multi-morbid elderly patients» (ESCAPE) study has been registered at the University of Göttingen Medical Centre (UMG Reg. No 02853) and the German Clinical Trials Register (DRKS00025120).